IMPLEMENTATION OF MSME DIGITALIZATION AS AN EFFORT TO EXPAND MARKET ACCESS - Putri, Griselda Amanda Archiey; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The research aims to analyze the implementation of digitalization as a strategy to expand market access and improve operational efficiency. Method: A qualitative approach was employed through in-depth interviews, field observations, and documentation, analyzed using policy implementation variables including communication, resources, disposition of implementers, and bureaucratic structure. Results: The findings reveal that the use of social media platforms such as WhatsApp and Instagram significantly increases consumer reach and sales revenue, while also creating opportunities for product innovation. Nonetheless, challenges remain in terms of limited technological capacity and inadequate mentoring support, which hinder broader adoption. Novelty: This study contributes by linking MSME digitalization practices with policy implementation theory, emphasizing the importance of government support in providing structured digital literacy programs and accessible platforms tailored for MSMEs, thereby ensuring more inclusive and sustainable digital transformation in the local economy.